2005
DOI: 10.1590/s1516-44462005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between binge-eating episodes and self-perception of body weight in a nonclinical sample of five Brazilian cities

Abstract: Relationship between binge-eating episodes and self-perception of body weight in a nonclinical sample of five Brazilian cities Relação entre episódios de compulsão alimentar e autopercepção do peso corporal em uma amostra não-clínica em cinco cidades brasileiras A b s t r a c t Objective: To investigate the relationship between binge-eating episodes and a perception that body weight is above the ideal in a sample of customers interviewed at shopping malls in five Brazilian cities. Methods: In 1999, data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
0
22
0
7
Order By: Relevance
“…In this study, women were asked about their selfperception of body weight in relation to what they perceived as ideal. 15 A perception that body weight was above the ideal was associated with binge-eating episodes, independent of BMI. 15 One study of Latin American adolescents from six different cities found a positive association between BMI or SES and body dissatisfaction measured with the Stunkard silhouettes, 16 yet, no studies have examined the relation between socioeconomic factors and perceptions of ideal and healthy body shapes or body dissatisfaction among adult women in Latin America.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, women were asked about their selfperception of body weight in relation to what they perceived as ideal. 15 A perception that body weight was above the ideal was associated with binge-eating episodes, independent of BMI. 15 One study of Latin American adolescents from six different cities found a positive association between BMI or SES and body dissatisfaction measured with the Stunkard silhouettes, 16 yet, no studies have examined the relation between socioeconomic factors and perceptions of ideal and healthy body shapes or body dissatisfaction among adult women in Latin America.…”
Section: Introductionmentioning
confidence: 96%
“…15 A perception that body weight was above the ideal was associated with binge-eating episodes, independent of BMI. 15 One study of Latin American adolescents from six different cities found a positive association between BMI or SES and body dissatisfaction measured with the Stunkard silhouettes, 16 yet, no studies have examined the relation between socioeconomic factors and perceptions of ideal and healthy body shapes or body dissatisfaction among adult women in Latin America. Kaufer-Horwitz et al 17 and Osuna-Ramírez et al 18 found a strong relation between BMI and current body shape perception obtained with the use of Stunkard silhouettes in Mexico; however, they did not study perceptions of ideal and healthy body shapes or body dissatisfaction.…”
Section: Introductionmentioning
confidence: 96%
“…Although the prevalence of BED diagnoses in the general population is low, isolated episodes of BE are more commonly observed in overweight individuals 3 , affecting between 30% and 70% of the overweight population 4 . In a population-based study conducted in the city of Rio de Janeiro, 20.6% of the women reported having had BE episodes in the past 6 months and 11.5% presented regular BE episodes (twice a week or more).…”
Section: Introductionmentioning
confidence: 99%
“…Also, there was a statistically significant association between binge eating episodes and Body Mass Index (BMI) and self-rated health 5,6 . In this context, Binge Eating Episodes (BEE) are commonly reported by obese individuals seeking weight-loss treatment 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Those evaluating recurrent binge eating have found lower prevalence rates than those who considered one or more episodes of binge eating (7)(8)(9)(10)(11) . Although BED is by definition regular occurrence of binge eating over a period of 6 months, studies evaluating shorter periods, e.g.…”
mentioning
confidence: 99%